Structural features and in vitro antiviral activities of sulfated polysaccharides from Sphacelaria indica - Bandyopadhyay, Shruti S.; Navid, Mojdeh Heidary; Ghosh, Tuhin; Schnitzler, Paul; Ray, Bimalendu (Phytochemistry, 2011)
Many viruses display affinity for cell surface heparan sulfate proteoglycans with biological relevance to virus entry. This raises the possibility of the application of sulfated polysaccharides in antiviral therapy. In this study, we have analyzed xylogalactofucan- and alginic acid-containing fractions from Sphacelaria indica, a marine alga. The xylogalactofucan that has apparent molecular mass of 26±5kDa and negative specific rotation [α]D32 −71° (c 0.2, H2O) contains, inter alia, (1→3)-linked l-fucopyranosyl and d-galactopyranosyl residues. The algin (molecular mass: 21±5kDa) contains 41% guluronic and 59% mannuronic acid residues. The 50% inhibitory concentration (IC50) values of these macromolecules and their chemically sulfated derivatives against herpes simplex virus type 1 (HSV-1) were in the range of 0.6-10μgml−1 and they lacked cytotoxicity at concentrations up to 200μgml−1. The antiviral activity was dependent on the sulfate contents of the polysaccharides. The results support the feasibility of inhibiting HSV infection by direct interaction of polysaccharides with viral particles.